Antonia Rosa, Ignez Pereira, Antonia Rodrigues, Maria Ruth : regimes de verdades, gênero e a escrita de si em processos de defloramento em Cuiabá/MT (1920-1940) - Moreira, Mayara Laet (2020)
The investigative plot of this research has its starting point in the narration of the experiences lived by Antonia Rosa, Ignez Pereira, Antonia Rodrigues and Maria Ruth, who had their existential stories crossed by the establishment of a lawsuit for the crime of defloration that occurred in the city of Cuiabá, between the 1920s and the 1940s. The focus of the analysis lies in the letters that were attached in the course of the lawsuit, working both as evidence of defense and of prosecution. Between the lines of this historical source, it is possible to make considerations on the movements of invisible women. Writing letters creates opportunities for autonomy, for giving real meaning to their words, since at all times they have spoken about and for them. Looking into this documentary source is to see how these four women gave meaning to their daily activities (the commuting around the city, their loving relationships, their friendships, their relatives, etc.) and experienced the tensions between the laws of the State and the family as an institution, which they intended to locate and imprison them in a network of knowledge/power. The gender, as a category of analysis, theorized by Joan Scott, allows us to identify the discourses that grounded the common sense, the literature and the newspapers from the capital city of the state of Mato Grosso, in which place women and men were subjected to behavioral models, as well as those who substantiated the Regimes of Truth (legal, medical and pedagogical discourses), which sought to standardize relations between the sexes. The dialogue with the philosopher Michel Foucault is of utmost importance to highlight the processes of subjectivity of sexuality and behavior, as well as to positively examine the lives of the four women, in order to build a liberating action (from the impositions and social and political flows at a given time), at least, by writing.